2022
DOI: 10.1055/a-1788-9888
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to changes in viscosity and flow rate of a dedicated gel for gel immersion endoscopy

Abstract: Background and study aims Gel immersion endoscopy is a novel technique for securing the visual field during endoscopy. Clinical application of a dedicated gel for this technique with an appropriate viscosity to prevent mixing with blood and its efficacy was reported. The aim of this study was to evaluate changes in gel viscosity and flow rate under different conditions. Methods The viscosity of the gel after injection and flow rate were measured under various conditions changing the injection route a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…VISCOCLEAR (Otsuka Pharmaceutical Factory, Tokushima, Japan), which is designed for gel immersion endoscopy, has the appropriate viscosity to prevent mixing with blood and/or residue immediately and facilitates securing the visual field during endoscopy [1]. Hiraki, et al reported that when gel stored at room temperature (25 °C) was injected via the water jet channel using a water pump at the maximum power setting, its viscosity significantly decreased to 321 mPa • s [2], which is close to 231 mPa • s, the lower limit of viscosity required for effectiveness [1]. Hiraki et al also reported that the viscosity of the gel, which was 768 mPa • s at 25 °C, increased to 998 mPa • s when stored at 4 °C [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…VISCOCLEAR (Otsuka Pharmaceutical Factory, Tokushima, Japan), which is designed for gel immersion endoscopy, has the appropriate viscosity to prevent mixing with blood and/or residue immediately and facilitates securing the visual field during endoscopy [1]. Hiraki, et al reported that when gel stored at room temperature (25 °C) was injected via the water jet channel using a water pump at the maximum power setting, its viscosity significantly decreased to 321 mPa • s [2], which is close to 231 mPa • s, the lower limit of viscosity required for effectiveness [1]. Hiraki et al also reported that the viscosity of the gel, which was 768 mPa • s at 25 °C, increased to 998 mPa • s when stored at 4 °C [2].…”
mentioning
confidence: 99%
“…Hiraki, et al reported that when gel stored at room temperature (25 °C) was injected via the water jet channel using a water pump at the maximum power setting, its viscosity significantly decreased to 321 mPa • s [2], which is close to 231 mPa • s, the lower limit of viscosity required for effectiveness [1]. Hiraki et al also reported that the viscosity of the gel, which was 768 mPa • s at 25 °C, increased to 998 mPa • s when stored at 4 °C [2].…”
mentioning
confidence: 99%